Advancing Renewable Energy Through State Priorities and Sustainable Transition Policies - Shabanov, Zeynaddin; Hasanov, Aghasalim; Abdullayev, Kamran; Pironti, Vicente; Vivekanantharasa, Raveenthiran (SocioHumania: Journal of Social Humanities Studies, 2025)
This study analyzes the strategic role of digital transformation in accelerating the development of the green economy in Azerbaijan. As global economic systems shift toward sustainability-oriented models, Azerbaijan has begun integrating digital technologies—such as smart energy systems, geographic information platforms, and digital monitoring tools—into its environmental and economic policies. These initiatives are designed to reduce carbon intensity, enhance resource efficiency, and modernize industrial sectors in alignment with international climate standards. The study employs a qualitative library-based approach supported by content analysis to assess state programs, institutional reforms, and policy documents related to digital governance and renewable energy deployment. The findings indicate that digital solutions facilitate transparent decision-making, optimize energy consumption, and support ecological innovations, making them essential components of Azerbaijan’s national development agenda. However, the transition remains constrained by infrastructural disparities, limited technological competencies, and regulatory gaps. The study argues that sustainable development goals cannot be fully realized without comprehensive digital integration, institutional coordination, and capacity-building initiatives. Thus, digitalization is not merely a supportive tool but a foundational mechanism for the advancement of the green economy and long-term socio-economic transformation in Azerbaijan.